2017
DOI: 10.1302/2046-3758.611.bjr-2016-0088.r2
|View full text |Cite
|
Sign up to set email alerts
|

Computational study on the effect of malalignment of the tibial component on the biomechanics of total knee arthroplasty

Abstract: ObjectivesMalalignment of the tibial component could influence the long-term survival of a total knee arthroplasty (TKA). The object of this study was to investigate the biomechanical effect of varus and valgus malalignment on the tibial component under stance-phase gait cycle loading conditions.MethodsValidated finite element models for varus and valgus malalignment by 3° and 5° were developed to evaluate the effect of malalignment on the tibial component in TKA. Maximum contact stress and contact area on a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Our study found that the KA tibial plateau was less stable than the MA and valgus tibial cut when there was no sclerosis in the medial tibia. Previous studies [13, 21, 29, 30] have shown that the tibial plateau had the worst stability in the absence of sclerosis after 2.5° varus tibial cut [30] compared to 3°varus tibial cut [12, 13]. This is consistent with the results of our study comparing the prosthesis stability of the three groups without sclerosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study found that the KA tibial plateau was less stable than the MA and valgus tibial cut when there was no sclerosis in the medial tibia. Previous studies [13, 21, 29, 30] have shown that the tibial plateau had the worst stability in the absence of sclerosis after 2.5° varus tibial cut [30] compared to 3°varus tibial cut [12, 13]. This is consistent with the results of our study comparing the prosthesis stability of the three groups without sclerosis.…”
Section: Discussionsupporting
confidence: 92%
“…Since a motion model was not used, the profile above the spacer could be omitted and replaced with a platform [17, 18]. We neglected the element of bone cement as in previous research models [12, 19, 20].…”
Section: Methodsmentioning
confidence: 99%
“…7). Such studies have been performed in both FE and MBD models (Essner et al, 2011;Kang et al, 2018a;Kang et al, 2016;Kang et al, 2017f;Kang et al, 2018b;Kang et al, 2018c;Kang et al, 2018e;Kang et al, 2019b;Kang et al, 2018g;Kuriyama et al, 2014;Marra et al, 2018;Suh et al, 2017;Thompson et al, 2011). Investigations have included pre-or post-clinical evaluation for translation and rotation in coronal and sagittal planes.…”
Section: Application Of Computational Simulation In Pre-or Post-clinimentioning
confidence: 99%
“…Many studies have also examined misalignment of the tibial component (Kang, Kwon, Son, Kwon, Lee and Koh, 2018a;Kang et al, 2018d;Kang, Kwon, Son, Kwon, Lee and Koh, 2018g;Kuriyama, Ishikawa, Furu, Ito and Matsuda, 2014;Suh, Kang, Son, Kwon, Baek and Koh, 2017). Kuriyama et al evaluated traction forces in the LCL and MCL with a malrotated tibial component during squatting using computational simulation (Kuriyama, Ishikawa, Furu, Ito and Matsuda, 2014).…”
Section: Application Of Computational Simulation In Pre-or Post-clinimentioning
confidence: 99%
“…Coronal alignment of the TKA has been shown to influence the load in the medial compartment, which my effect the wear of the polyethylene, and ligamentous stability, laterally. 11 Femoral rotation has been demonstrated to have a direct effect on the force transmitted through the medial tibiofemoral compartment and patellofemoral joint, with internal rotation increasing the force through these compartments. 12 The majority of TKA designs sacrifice the anterior cruciate ligament, and others also sacrifice the PCL, which changes the joint kinematics.…”
mentioning
confidence: 99%